ANALYSIS OF FINANCIAL RATIOS TO ASSESS COMPANY'S FINANCIAL PERFORMANCE - Tita Kartika; Fanji Farman (Jurnal Ekonomi, 2022)
Based on the findings of the company's financial ratio analysis, this study seeks to describe the financial performance of banks. According to the data used, namely secondary data, the method employed in this investigation is a documentation technique, namely data collection techniques by reading, studying, and analysing archives - archives or financial records related to research. The type of research used in this study is descriptive research using secondary data as the primary data. The findings of the banking ratio study indicate that PT Bank Rakyat Indonesia Persero Tbk's financial performance is in very good condition and meets Bank Indonesia criteria.